Li'l Abner [videorecording (DVD)] - Frank, Melvin, 1913-1988; Palmer, Peter, 1931-; Parrish, Leslie; Kaye, Stubby; Newmar, Julie, 1933-; Capp, Al, 1909-1979 (Widescreen DVD collection., 2005)
Based on the beloved cartoon strip from Al Capp, Li'l Abner takes place in the hillbilly town of Dogpatch. When the city is chosen as a test site for A-bombs, its colorful citizens take up the good fight, with lots of fun and merriment.